Phytoplankton Community Structure of Oxbow Lake-Sinau, Kapuas Hulu, West Kalimantan - junardi; Candramila, Wolly; Mundiarto, Sigit (Biospecies, 2019)
The Sinau Lake is one of the oxbow lakes in Kapuas Hulu, West Kalimantan, which will be used for various purposes, but limnological data is not available. The research objective was to obtain data on the structure of the phytoplankton community and the water quality conditions of Sinau Lake so that it could be used as preliminary data for management and utilization. Samples were taken using purposive sampling method. Water quality is still good with a high plankton diversity index, low dominance and high evenness. Water quality still support the life of aquatic biota or aquaculture.